Job Loss and Changes in Personality - Evidence from Plant Closures - Silke Anger; Georg Camehl; Frauke H. Peter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Personality traits and other non-cognitive skills have long been considered to be quite stable over adulthood. Economic studies on non-cognitive skills as determinants of educational and labor market outcomes therefore assumed their stability over time to rule out reverse causality. However, recent evidence from psychology suggests that the stability assumption may not always hold. Our paper aims at identifying causal effects of job loss on changes in personality and thereby at complementing recent studies in economics and psychology on the stability of personality traits. We use data from the German Socio-Economic Panel Study (SOEP) for the years 2004 to 2014 which include measures of the Big 5 personality inventory with two repeated measurements as well as detailed employment information. We focus on plant closures and dismissals, which have been widely used as an exogenous event in the literature. Our results based on linear regression models and on a novel econometric method to account for selectivity suggest that job loss leads to a drop in emotional stability. The other dimensions of the Big 5 personality inventory remain (nearly) unchanged. Moreover, the drop in emotional stability is more pronounced for individuals who do not find re-employment. Individuals who face changes in their non-cognitive skills following a job loss may find it more difficult to re-enter employment, which may explain duration dependence of unemployment.
Keywords: I12; J24; J65; 330